Active du/dt Filtering for Three Phase Motor Drive Applications - Kohlhepp, Benedikt; Ye, Tianlun; Dürbaum, Thomas (ICPE 2023-ECCE Asia - 11th International Conference on Power Electronics - ECCE Asia: Green World with Power Electronics, 2023)
The performance of modern wide bandgap semiconductors cannot be fully exploited in inverters for motor drive applications, since faster switching is not possible due to the high du/dt causing overvoltages due to reflections on cables and EMI issues. Classical LC filters are also not suitable, as these limit power density. This situation calls for an active du/dt filter implementing intelligent switching transitions of the power semiconductors to ensure high efficiency and low du/dt at the output simultaneously. Theoretically, the modulation scheme can deliver ideal smooth transitions. However, in practical setups non-idealities cause severe oscillations of the resonant tank. This paper studies the origin of this oscillation and proposes a compensation method to successfully reduce the undesired oscillation.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Active du/dt filter; GaN; Inverter; Nonidealities

Adaptive dead time in high frequency GaN-Inverters with LC output filter - Kohlhepp, Benedikt; Kübrich, Daniel; Tannhaeuser, Marvin; Dürbaum, Thomas (10th International Conference on Power Electronics, Machines and Drives, PEMD 2020, 2020)
Keywords: Gan-inverter; Adaptive dead time; Reverse conduction losses; LC output filter

A Novel Combination of Algorithms for Accelerated Convergence to Steady-State - Kohlhepp, Benedikt; Göttle, Jens; Schmidt, Eva; Dürbaum, Thomas (PCIM Europe 2018, 2018)
Due to a high production quantity and ongoing miniaturization of switched mode power supplies for consumer products, a high power density is desirable. In order to achieve this goal, a high switching frequency with low losses is necessary at the same time. With these requirements, the cost aspect must not be ignored under any circumstances. Therefore, parameter variations of the components building the power supply must be carried out for many operating points of each parameter set to take the full load as well as the part load efficiency into consideration. This requires a very fast simulation model as on the one hand transients decay very slowly within switching converters and on the other hand to cope with the vast parameter range occurring during optimization. Therefore, this paper presents a novel combination of algorithms yielding the steady-state solution of switch mode power supplies through simulation. A mixture of numerical and analytical methods to reach the steady-state operation is used within this work. The proposed simulation procedure is applied to a conventional DC-DC converter to prove its reliability and performance.

A Novel Test Setup for Arbitrary PWM Converter Excitations of Nonlinear Inductors - Kaiser, Jeremias; Au, Calvin; Kohlhepp, Benedikt; Dürbaum, Thomas (PCIM Europe 2023 - International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2023)

Common Mode of Inverters: Survey and Study of Filter Placement on Grid and Load Side - Kohlhepp, Benedikt; Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2022)
Inverters driving motors fed by the grid require PFC stages with a suitable filter. Designing the filter requires knowledge of the noise level. As cm-noise prediction of inverters is quite difficult, this paper studies an inverter’s cm-noise by experiments. It is shown that high levels can be expected from inverters, when no filter is applied. Thus, this paper analyzes the cm-noise paths and derives a filter placed between grid and inverter. An alternative position of the filter is between inverter and motor. This configuration requires a smaller common mode choke to comply with EMI standards.
CRIS-Team Scopus Importer:2022-06-10

Cost-Effective Test Setup for Measuring Threshold Voltage Shift of GaN-HEMTs under Long-Term Drain-Voltage Stress - Breidenstein, Daniel; Kohlhepp, Benedikt; Dürbaum, Thomas (2023 IEEE 10th Workshop on Wide Bandgap Power Devices & Applications (WiPDA), 2023)
GaN-HEMTs offer low on-resistances and low capacitances, making them attractive candidates for high efficient power electronic converters. In this field of application, the normally-off transistor is the preferred structure but can exhibit threshold voltage instability problems. Undesired threshold-shifts can lead to increased switching losses or unintended turn-on events. Typically, the dedicated and expensive semiconductor device characterization equipment is unavailable in application-oriented power electronics labs. Therefore, this paper proposes a cost-effective test setup based on standard laboratory equipment to measure the threshold voltage shift due to static long-term drain voltage stress. The test procedure alternates between stress periods and short measurement pulses, during which the transfer characteristic is recorde

Detailed Simulation Model of an Asymmetrical Half-Bridge PWM Converter with Synchronous Rectification including Parasitic Elements - Kohlhepp, Benedikt; Zeller, Valentin; Barwig, Markus; Dürbaum, Thomas (2020 22nd European Conference on Power Electronics and Applications, EPE 2020 ECCE Europe, 2020)
The asymmetrical half-bridge converter implemented with GaN-switches represents a great candidate for achieving high power density and high efficiency. These requirements call for the implementation of a synchronous rectifier on the secondary side to push the efficiency. Furthermore, higher switching frequencies lead to smaller passive components needed for compact power supplies. In order to gain accurate and reliable simulation results for these high switching frequencies, this paper presents a detailed simulation model featuring parasitics of all semiconductors and transformer capacitances. Besides current and voltage waveforms of one switching cycle, this model allows for studying ZVS transitions as well. Measurements on a practical test setup deliver waveforms very close to the simulation results and thus prove the validity of the simulation model.
Created from Fastlane, Scopus look-up
Keywords: Gallium Nitride (GaN); Simulation; Soft switching; Switched-mode power supply; ZvS converters

Efficiency Comparison of an Asymmetrical Half-Bridge PWM Converter with Schottky and Synchronous Rectification - Kohlhepp, Benedikt; Barwig, Markus; Dürbaum, Thomas (53rd International Universities Power Engineering Conference, UPEC 2018, 2018)
Keywords: Efficiency Comparison; Asymmetrical Half-Bridge PWM Converter; Synchronous Rectification; Schottky Rectifier

Experimental Study of the Coss-Losses Occurring During ZVS Transitions – Emphasis on Low and High Voltage GaN-HEMTs - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (CIPS 2020, 2020)
GaN-HEMTs offer completely new possibilities for the development of advanced power electronics. GaN devices enable, due to the lower parasitics, higher switching frequencies. However, high efficiency at high frequent operation requires ZVS. It is typically assumed that the ZVS transitions are lossless. However, at least in case of Si-SJ-MOSFET experiments show that sometimes losses occur during charging and discharging of the output capacitances. For this reason, this paper examines the losses occurring during ZVS by employing Sawyer Tower measurements of GaN devices. Losses are meas-ured depending on the amplitude of the Drain-Source voltage and frequency, finding that these are negligibl

Extraction of Parasitic Elements of a Printed Circuit Board applied to a GaN Half-Bridge - Kohlhepp, Benedikt; Faber, Samuel; Kaiser, Jeremias; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2022)
Modern semiconductors like GaN enable high efficient converter designs and fast switching transitions. In order to achieve full performance of these components in terms of switching behavior, parasitic inductances of the switching cell must be accurately known and minimized, since they have a significant influence on the switching transitions. Due to optimized device packages and PCB layouts, these are in the range of nH or even pH, which make accurate measurements very difficult or impossible. Thus, field simulations are the only way to obtain self and mutual inductances of the commutation loop as well as of the gate loops. This paper shows that commutation loop inductances below 1 nH are possible. The common source inductance, which represents the common conductive path as well as mutual couplings, is in the range of pH for a GaN-half-bridge.
CRIS-Team Scopus Importer:2022-06-10

Full gan asymmetrical half-bridge pwm converter with synchronous rectifier for a high efficient 90 W laptop charger - Kohlhepp, Benedikt; Zeller, Valentin; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Since modern semiconductors, like GaN-and SiC-devices, provide superior characteristics over conventional Si-devices, their contribution to a DC/DC converter is studied here. First, the paper describes two different simulation models for the asymmetrical half-bridge converter. Based on this, a proper simulation routine is used to find an optimized design for a given specification using GaN-devices for the half-bridge and the synchronous rectifier. After that, a practical test setup validates the simulation results and shows superior performance compared to converters built with conventional Si-devices. The full GaN converter features higher power density as well as higher efficiency.
CRIS-Team Scopus Importer:2021-11-05

GaN-Half-Bridge for Core Loss Measurements under Rectangular AC Voltage and DC Bias of the Magnetic Flux Density - Stenglein, Erika; Kohlhepp, Benedikt; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (IEEE Transactions on Instrumentation and Measurement, 2020)
An accurate calculation of core losses is essential for the design of switched-mode power supplies. However, such predictions remain a challenge as core losses depend on various parameters, e.g., the waveform of the magnetic flux density, including its fundamental frequency and dc bias. To investigate the influence of dc bias, core loss measurements usually impose a dc current and, thus, dc bias of the magnetic field strength on ungapped toroid samples. However, hardware designers require the ac and dc excitation of the magnetic flux density. Therefore, this article proposes a half-bridge configuration to impose rectangular ac voltages on the core under test (CUT). By performing a pulsed operation in combination with an iteration method, the desired ac and dc excitation of the magnetic flux density can be obtained. GaN-HEMTs have been applied as they allow a printed circuit board design with low parasitic inductances and thus avoid ringing. The measurement setup is able to characterize magnetic materials at high frequencies for triangular magnetic flux density waveforms, including dc bias and different duty cycles. In addition, the influence of magnetic history on core losses can be studied, an issue usually not addressed in the literature. Moreover, the relationship between the dc bias of the magnetic field strength and the dc bias of the magnetic flux density is investigated. A simple functional approach, e.g., by using the initial magnetization curve, does not suffice to describe this relationship. Accordingly, core losses should be derived as a function of dc bias of the magnetic flux density for the results to be of practical use to hardware designers.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Core loss; dc bias; half-bridge; hysteresis; measurement; rectangular voltage

GaN-HEMT Based Test Setup for Measurement of Core Losses Under DC-Bias - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (ETG-Fachbericht, 2022)
For power electronics designers, accurate magnetic core loss predictions play a major role in converter design and optimization. Unfortunately, loss predictions are still a difficult task, since manufacturers do not provide enough information in their data sheets for the many parameters affecting the losses. Especially, core loss results under DC-bias of the flux density are missing. Thus, this paper presents a method for these core loss measurements. Instead of using the most common AC metering approach, this paper relies on a DC current and voltage measurement at the input of the inductor loss test setup. After introducing the test setup and its operation principle, the instrumentation and its requirements is studied. Measurements with a device under test deliver the core losses under DC-bias, which show an increase of losses of 13% due to DC-bias in flux density. These results demonstrate the necessity to perform core loss measurement under DC-bias.
CRIS-Team Scopus Importer:2022-09-02

GaN Improves Efficiency of an Asymmetrical Half-Bridge PWM Converter with Synchronous Rectifier - Kohlhepp, Benedikt; Barwig, Markus; Dürbaum, Thomas (PCIM Europe 2019; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2019)
As the asymmetrical half-bridge PWM converter achieves high efficiency by employing zero voltage switching (ZVS), it is a highly promising candidate for switch mode power supplies. Nevertheless, high efficiency in low output voltage applications requires synchronous rectification. Even though a simple replacement of the Schottky rfectifier diode by a synchronous rectifier shows promising results by simulation, practical setups reveal great deviations. Strong damped oscillations during turn-off of the synchronous rectifier induce enormous losses. Using a GaN-FET as synchronous rectifier featuring its very good parasitic properties solves the problem during turn-off. Therefore, this paper analyzes an asymmetrical half-bridge PWM converter design employing a GaN-HEMT as synchronous rectifier, directly focusing on solving the identified proble

High frequency ZVS GaN-inverter with adaptive dead time - Kohlhepp, Benedikt; Förster, Thomas; Dürbaum, Thomas (2021 56th International Universities Power Engineering Conference: Powering Net Zero Emissions, UPEC 2021 - Proceedings, 2021)
This paper presents a zero voltage switching (ZVS) inverter and the corresponding modulation scheme, which uses variable and fixed switching frequency operation during the sinusoidal period to limit the switching frequency range. It is suitable for generating sinusoidal output waveforms and ensuring lossless switching over the entire fundamental period. ZVS requires a sufficiently long dead time during both switches are turned off. Typically, standard modulation schemes apply a fixed dead time. First experiments operate the ZVS inverter with a fixed dead time. Despite achieving lossless switching, unexpected high device temperatures of the Gallium Nitride half-bridge switches occur. The origin of these high temperatures need to be figured out in order to minimize the losses of the power stage. A study shows that significant reverse conduction losses occur during the half-bridge's dead time. Thus, this paper introduces an adaptive dead time method, which shows its effectiveness at an experimental setup by reducing the semiconductor's device case temperature by 10 K. Since the computational effort for this optimal procedure is relatively high, the paper finally presents a simplified, computationally less costly variant that achieves almost the same improvements regarding the device temperatures.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Adaptive dead time; GaN; Inverter

How to choose the optimal gan-hemt for a hard switching application – a guide - Dobusch, Julian; Schwanninger, Raffael; Kohlhepp, Benedikt; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Modern GaN-HEMTs offer beneficial advantages over traditional Si-MOSFETs. GaN-HEMTs exhibit much lower stored charge (QOSS ) while providing identical conduction losses (RDS,On ). However, choosing the right switch is not straight forward and the non-linear relation of voltage and charge has to be taken into account. This paper presents a guide on how to select the right switch to minimize conduction and switching losses considering the crucial influence of all switches on the switching losses.
CRIS-Team Scopus Importer:2021-11-05

Improving Efficiency of an Asymmetrical Half-Bridge PWM Converter with Synchronous Rectification by a Modified Design Process - Kohlhepp, Benedikt; Barwig, Markus; Dürbaum, Thomas (10th International Conference and Expositions on Electrical And Power Engineering, EPE 2018, 2018)
Keywords: Design Process; Schottky Rectifier; Improved Efficiency; Synchronous Rectifier

In-Depth Study of the Parasitic Capacitances of a Half-bridge Circuit - Faber, Samuel; Kohlhepp, Benedikt; Dobusch, Julian; Kaiser, Jeremias; Dürbaum, Thomas (25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe), 2023)
Wide bandgap power devices are pushing the trend of increasing switching frequencies even further, giving rise to a frequency shift of EMC noise. As a result, parasitic elements gain significantly in importance. For this reason, parasitic capacitances of a half-bridge circuit PCB are studied by means of numerical simulations. After an introduction into the half-bridge circuit in terms of CM noise, the focus is layed on the simulation methods applied, the generation of a suitable simulation model as well as the development of a more intuitive equivalent circuit. Simulation results for typical measurement conditions are presented and compared with each othe

Inductor design considerations for overload conditions of lc-filters in high frequency gan-inverters - Kohlhepp, Benedikt; Barwig, Markus; Kübrich, Daniel; Roßmanith, Hans; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2020)
High frequency GaN inverters feature high power density and efficiency. Typically, they are used in conjunction with an output filter in order to keep high frequency noise away from the load. During overload conditions, while accelerating or braking, significantly higher output currents occur compared to nominal operation. Without dramatic oversizing the component, this can result in saturation of the filter inductance’s core in case of ferrite. Therefore, this paper proposes an air inductor as filtering element in order to tackle this problem. Small signal impedance measurements as well as results within a real inverter application demonstrate the feasibility of the designed air inductor.
CRIS-Team Scopus Importer:2020-08-28

Influence of the Rectifier's Output Capacitance on the ZVS Transition in Asymmetrical Half-Bridge PWM Converters - Kohlhepp, Benedikt; Barwig, Markus; Dürbaum, Thomas (ICPE 2019 - ECCE Asia - 10th International Conference on Power Electronics - ECCE Asia, 2019)
High sales quantities and an ongoing miniaturization of notebook power supplies require an improvement of their efficiency. In order to achieve a high power density, a high switching frequency in combination with low losses is necessary. The asymmetrical half-bridge PWM converter fits perfect for these requirements, as it allows zero voltage switching (ZVS) for the half-bridge MOSFETs, which is necessary for an efficient design. Furthermore, high efficiency requires the use of a synchronous rectifier. Unfortunately, measurements on a test setup reveal, that the parasitic output capacitance of the rectifier has a significant influence on the ZVS transition. This is due to the comparably very large output capacitance accompanied with low ohmic MOSFETs. For this reason, the paper examines the ZVS process of the input half-bridge considering the rectifier's parasitic output capacitance. Furthermore, the required dead time of the half-bridge is predicted, taking the parasitic capacitance into account.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Asymmetrical Half-Bridge PWM Converter; Synchronous Rectifier; Zero Voltage Switching

Measurement of Dynamic On-State Resistance of High-Voltage GaN-HEMTs under Real Application Conditions - Kohlhepp, Benedikt; Kuring, Carsten; Peller, Stefan; Kübrich, Daniel (22nd European Conference on Power Electronics and Applications (EPE'20 ECCE Europe), 2020)
GaN-HEMTs gain a lot of attention to power electronics engineers. However, they could exhibit increased on-state resistance due to charge trapping. This paper focusses on measuring this effect for high voltage devices. Measurements reveal an unexpected blocking voltage dependency of on-state resistance. Therefore, a second measurement setup serves as verificatio

Measuring and Modeling of Dynamic On-State Resistance of GaN-HEMTs - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (2019 21st European Conference on Power Electronics and Applications, EPE 2019 ECCE Europe, 2019)
GaN-HEMTs as switching devices impress with their very good properties and gain therefore a lot of attention from the power electronics community. However, some GaN devices may exhibit increased resistance during on-state due to charge trapping effects. As for designers of switch mode power supplies the internal structure of devices is concealed, measurements are the only way to gain information. This paper shows the measurement of the static on-state resistance of a GaN-HEMT. Furthermore, it quantifies the dynamic on-state resistance by measurement with a novel clamping circuit using a digitizer card with high resolution. Based on these results, it presents an easy to implement method for calculating conduction losses in the presence of dynamic on-state resistance.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Conduction losses; Gallium Nitride (GaN); Measurement; Modelling

Measuring of Dynamic On-State Resistance of GaN-HEMTs in Half-Bridge Application under Hard and Soft Switching Operation - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas; Tannhaeuser, Marvin; Hoffmann, Andreas (2019 IEEE ELECTRICAL POWER AND ENERGY CONFERENCE (EPEC), 2019)
CRIS-Team WoS Importer:2020-10-02

Method for compensating the effects of gan-hemts on the output voltage in inverters during dead time - Kohlhepp, Benedikt; Lanvermann, Tim; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2020)
By using GaN-HEMTs in three-phase inverters, significantly higher switching frequencies can be achieved compared to conventional Si-MOSFETs. However, as the switching frequency increases, the influence of the GaN-HEMTs on the waveform of the output voltage also rises during dead time. Therefore, this paper demonstrates a procedure that compensates the influence of dead time, reverse conduction of GaN-HEMTs and the switching transition.
CRIS-Team Scopus Importer:2020-08-28

Modulation Method to Reduce Losses in Inverters with LC-Filters - Kohlhepp, Benedikt; Kübrich, Daniel; Tannhaeuser, Marvin; Dürbaum, Thomas (23rd European Conference on Power Electronics and Applications, EPE 2021 ECCE Europe, 2021)
Keywords: Soft switching; Pulse Width Modulation (PWM); Voltage Source Inverter (VSI)

Modulation Strategy Comprising TCM with Frequency Limit and DPWM for Fast Switching GaN-Inverters - Kohlhepp, Benedikt; Dürbaum, Thomas (2021 IEEE 8th Workshop on Wide Bandgap Power Devices and Applications (WiPDA), 2021)

Non‐ideal behavior of ZVS inverter comprising variable and fixed frequency operation: Analysis, compensation, and verification - Kohlhepp, Benedikt; Dürbaum, Thomas; Heubeck, Jens (International Journal of Electrical Power & Energy Systems, 2022)
This paper presents a study of a two-level inverter. It proposes a modulation scheme for inverters featuring zero-voltage switching (ZVS) with both fixed and variable switching frequency operation. The control scheme uses a hybrid method to determine the switching actions of the half-bridge consisting of a current threshold detection circuit and predictions from numerical evaluations of fundamental waveforms of an ideal half-bridge circuit. Compared with conventional fixed frequency PWM inverters, the inverter in this study exhibits higher rms currents but eliminates switching losses. As several components in practical setups of the inverter inevitably introduce non-idealities, a study of these and their impact on the output waveforms follows. The study comprises the propagation delay of the current threshold detection circuit, the filter capacitance, and the DC-link capacitance. Our study demonstrates the need to consider these effects. We show that smooth output waveforms can be achieved for low and high voltage applications if these effects are properly taken into account in an experimental setup. The total harmonic distortion (THD) is used to evaluate the output waveform quality, which is 0.81% when all effects are properly considere

Novel DPWM modulation scheme for three-phase ZVS inverters - Kohlhepp, Benedikt; Dürbaum, Thomas (2021 56th International Universities Power Engineering Conference: Powering Net Zero Emissions, UPEC 2021 - Proceedings, 2021)
Most inverters driving electrical machines or for grid applications operate under hard switching conditions at fixed frequency. However, the resulting high switching losses from the hard switched operation limit the efficiency. Another approach uses triangular current mode to achieve zero voltage switching of the semiconductors, thus avoiding switching losses. Disadvantageously, this modulation scheme exhibits a huge current ripple especially during the extrema of the sine. To remedy this drawback, this paper studies a discontinuous pulse width modulation scheme by simulation, which avoids switching actions around the sinusoidal maximum and thus, reduces the overall current ripple. In order to be able to use this approach beneficially, the transitions to the intervals with no switching actions should be soft. This attenuates oscillations within the filter and thus provides the intended reduction in rms inductor current. Besides a lower rms current predicted by simulation, also significantly reduced losses of the inductor are to be expected.
CRIS-Team Scopus Importer:2021-10-22
Keywords: DPWM; Inverter; ZVS

Novel gan half-bridge configuration for the measurement of core losses under rectangular voltages and DC-bias - Stenglein, Erika; Kohlhepp, Benedikt; Kübrich, Daniel; Albach, Manfred; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2020)
An accurate calculation of core losses under rectangular voltages including DC-bias is useful for the design of switched-mode power supplies. Core loss measurements with DC-bias usually impose a DC current and thus DC-bias of the magnetic field strength on ungapped toroids. However, hardware designers require the AC and DC excitation of the magnetic flux density for the results to be of practical use. Therefore, this paper proposes a novel GaN half-bridge configuration to measure core loss under rectangular voltages at high frequencies. A new combination of pulsed operation and iteration method sets the desired DC-bias of the magnetic flux density.
CRIS-Team Scopus Importer:2020-08-28

PCB Layout Parasitics Extraction of a GaN Half-Bridge: Simulation and Experimental Validation - Kohlhepp, Benedikt; Faber, Samuel; Kübrich, Daniel; Dürbaum, Thomas (25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe), 2023)
Commutation loop inductance is on everyone’s lips in power electronics, due the relevance for switching transitions and switching losses. In most cases, this inductance is obtained by using numerical field simulations. However, confidence in the simulation results requires validation by measurements. Especially for designs employing wide bandgap semiconductors, minimized commutation loop inductance is crucial for full performance of the semiconductors. Applying optimized packages and PCB layouts results in commutation loop inductances below 1 nH, which makes its experimental extraction challenging. Therefore, the paper studies a method for commutation inductance measurement based on a resonance of a modified DC-link capacitor with this inductance. The measurement of a GaN-half-bridge’s commutation loop complies with results from simulation, demonstrating that the measurement method is applicable for commutation inductance in sub-nH rang

Radio Disturbance Evaluation of Si-and GaN-Inverters - Kohlhepp, Benedikt; Dobusch, Julian; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2023)
Inverters are widely used to drive electrical machines. Due to their switching operation, these devices inevitably generate EMC emissions. The demand for high efficiency leads to fast switching (high du/dt) inverters, which do not only emit conducted EMI but also radiated disturbances. Thus, this paper studies radiated emissions of different inverter configurations by using the easily applicable radio disturbance method instead of the cumbersome and time consuming measurements in a chamber. The study reveals that for conventional Si-inverters, shielding of the cables between inverter and motor as well as a metal case do not deliver a sufficient reduction of emissions below 100 MHz. Recently, GaN-devices are used in inverters. Due to their higher switching speed (higher du/dt) emissions may increase further, while their switching losses are reduced. In order to mitigate low frequency radiated emissions, a LC-filter is required. When applying proper shielding, low emissions at high frequencies can be achieved. The paper demonstrates that the radio disturbance measurement method can be an attractive alternative to the semi anechoic chamber during the development phase.
CRIS-Team Scopus Importer:2024-12-16

Study on Commutation Loop Inductance and Current Distribution to DC-link Capacitors in a GaN Half-bridge - Kohlhepp, Benedikt; Faber, Samuel; Kaiser, Jeremias; Dürbaum, Thomas (24th European Conference on Power Electronics and Applications, EPE 2022 ECCE Europe, 2022)
Modern wide bandgap power semiconductors allow for increased efficiency compared to conventional semiconductors by faster switching transients. In order to harness the full performance from these components, parasitic inductances must be minimized. FEM simulations can deliver the parasitic inductances and thus, can be used to optimize the PCB layout and the placement of semiconductors and DC-link capacitors. Also cost constraints apply to most of the power electronic circuits. FEM simulations can facilitate the determination of cost optimized designs by reducing the amount of DC-link capacitors. Therefore, the current distribution incorporating the DC-link capacitors is required. An analysis of a GaN half-bridge shows the potential to omit one poorly utilized MLCC capacitor.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Gallium Nitride (GaN); Half-bridge; Parasitic inductance

Switching loss estimation of gan-hemts by thermal measurement procedure - Kohlhepp, Benedikt; Kübrich, Daniel; Schwanninger, Raffael; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Modern semiconductors like GaN and SiC enable high efficient power conversion and provide superior switching behavior. For achieving high efficient converter designs, reliable data concerning losses is vital. Due to the high voltage and current slew rates during switching, the conventional double pulse test cannot be beneficially applied when using GaN to gain results concerning switching losses. Thus, this paper proposes a novel procedure to estimate switching losses by means of thermal measurements. A characterization of the test setup using DC currents links the occurring device temperatures during switching operation to power losses. First measurements prove the applicability of the procedure to a 100 V GaN device.
CRIS-Team Scopus Importer:2021-11-05

Switching Loss Measurement-A Thermal Approach Applied to GaN-Half-Bridge Configuration - Kohlhepp, Benedikt; Kübrich, Daniel; Dürbaum, Thomas (23rd European Conference on Power Electronics and Applications, EPE 2021 ECCE Europe, 2021)
Keywords: Measurement; Gallium Nitride (GaN); Switching losses

Test Setup for Dynamic ON-State Resistance Measurement of High- And Low-Voltage GaN-HEMTs under Hard and Soft Switching Operations - Kohlhepp, Benedikt; Kübrich, Daniel; Tannhauser, Marvin; Hoffmann, Andreas; Dürbaum, Thomas (IEEE Transactions on Instrumentation and Measurement, 2020)
GaN-HEMTs impress with excellent properties, and therefore power electronics engineers pay a lot of attention to them. However, during switching operation some devices show increased ON-state resistance. Since, for switch mode power supply designers, the internal device structure is not apparent, measuring the ON-state resistance under the targeted operating conditions is the only method to gain this information. In order to characterize the dynamic ON-state resistance, this article proposes a clamping circuit for accurate measurement. Using a high-resolution digitizer card ensures precise results. The presented measurement setup allows to measure the ON-state resistance under hard and soft switching conditions with parameters of the intended application. In inverter applications, each switch works under hard as well as soft switching. Therefore, the transition between these two operating modes must also be studied in detail. Finally, an extension of the clamping circuit is presented allowing measurements with high-voltage GaN-HEMTs as well. The initial results verify the improved setup.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Clamping circuit; dynamic ON-state resistance measurement; high- and low-voltage GaN-HEMTs

Test Setup for Loss Measurements of Inductive Components by using GaN-HEMTs - Kohlhepp, Benedikt; Peller, Stefan; Kübrich, Daniel; Dürbaum, Thomas (2020 IEEE 21st Workshop on Control and Modeling for Power Electronics, COMPEL 2020, 2020)
This paper describes and verifies a measurement setup based on GaN semiconductors to characterize losses of inductive components used in switched-mode power supplies. Due to insufficient datasheet parameters, especially core losses occurring in inductive components cannot be accurately calculated by simulation. Furthermore, proximity losses within windings are difficult to obtain due to inhomogeneous field distributions within inductive components. Therefore, the ability to measure losses of inductive components plays an important role in the development of power supplies. Conventional test setups use the DUT's AC voltage and current to obtain the losses. Based on [1] this paper designs and verifies a circuit that allows for loss measurements of inductive components by only employing DC voltage measurements. After a presentation of the measuring principle and the resulting test setup realization, it is verified by measuring the well-defined losses of an air coil.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Core loss; Half-bridge; Power measurement; Rectangular voltage

Test Setup to Study Threshold Voltage Shift of GaN-HEMTs Under Short- and Long-Term Gate and Drain Bias - Kohlhepp, Benedikt; Breidenstein, Daniel; Dürbaum, Thomas (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2024)
GaN-HEMTs offer low on-state resistance and fast switching transitions. Thus, these devices represent attractive candidates to build high efficient power converters with high power density. Unfortunately, charge-trapping effects deteriorate on-state resistance and affect threshold voltage. Undesired threshold voltage shifts impact the switching losses and can cause false turn on due to miller currents. As data sheets lack information regarding threshold voltage instabilities, power electronics engineers need to conduct own measurements. Since charge trapping exhibits time constants in the range of microseconds up to hours, short-as well as long-term studies are required. Furthermore, trapping exhibits several dependencies on operation parameters like temperature as well as drain and gate bias. This calls for a custom test setup capable of acquiring threshold voltage under application-oriented conditions. The one proposed in this paper only requires standard laboratory equipment typically present in every power electronics lab. The test setup alternates between stress or relax phases and short measurement pulses for extracting the threshold voltage under certain conditions. The results show a strong influence of the drain and gate bias on the threshold voltage with long time constant

Test setup using DC metering approach for loss measurements of inductive components – principle, characterization, validation and application - Kohlhepp, Benedikt; Kübrich, Daniel; Peller, Stefan; Dürbaum, Thomas (Iet Power Electronics, 2021)
Accurate loss estimation of magnetic components is crucial for power electronics engineers. Unfortunately, loss predictions remain a quite challenging task, as these depend on many parameters and manufacturers typically do not deliver a sufficient database for precise loss estimations. Therefore, this paper revisits an approach allowing loss measurements. In contrast to the most common used approach using alternating current (AC) waveforms to gain information about the losses, this approach relies on measuring direct current (DC) voltage and current. After characterizing the experimental setup, air inductors serve as references to validate the approach. In a first step, the test setup is used to extract core losses with and without DC bias by designing a special device under test (DUT) featuring low winding loss. Furthermore, this paper demonstrates that the test setup is also able to gain the overall losses of complete magnetic components by using the DC metering approach.
CRIS-Team Scopus Importer:2021-06-18

Three-Phase ZVS Inverter with Variable and Fixed Frequency Operation based on GaN Semiconductors - Kohlhepp, Benedikt; Lutsch, Michael; Dürbaum, Thomas (24th European Conference on Power Electronics and Applications, EPE 2022 ECCE Europe, 2022)
As high efficiency is on everyone's lips, this paper studies an inverter using a ZVS modulation scheme promising high efficiency. It uses triangular current mode (TCM) to minimize the ripple while maintaining ZVS. In order to fulfill the required power density, high switching frequencies should be applied. Current threshold detection circuits in combination with this modulation scheme turn the inverter's legs into current sources. Since all phases of the inverter are tied together at the load's star point, there might be issues, if slight current threshold errors exist within the inverter. In order to demonstrate that the modulation scheme can handle situations with and without connection of the load's neutral point to the DC-link midpoint, both configurations are studied in a practical setup. The practical test setup gives satisfactory results with respect to the quality of the output waveforms using the THD of the currents.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Gallium Nitride (GaN)>>; Voltage Source Inverter (VSI); ZVS converters